2004
DOI: 10.1002/hyp.5746
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of moisture dynamics of litter layers—the effects of rainfall conditions and leaf shapes

Abstract: Abstract:The effects of rainfall conditions and the morphological characteristics of leaves on the moisture dynamics of litter layers were investigated. Maximum water storage capacity and interception storage capacity under various rainfall conditions were evaluated for two contrasting litter types: a needle-leaf type, represented by Cryptomeria japonica leaves; and a broad-leaf type, represented by Lithocarpus edulis leaves. An artificial rainfall simulator was applied to measure each litter type's intercepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
183
4
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(227 citation statements)
references
References 15 publications
(24 reference statements)
17
183
4
17
Order By: Relevance
“…These studies indicate that storage capacity of litter layers increased linearly to litter mass (Putuhena and Cordery, 1996;Sato et al, 2004). Also Sato et al (2004) demonstrated that rainfall intensity increased C min and C max of litter layers. For example C min increased from 0.44 to 1.03 mm for Cryptomeria japonica (D. Don) and from 1.33 to 1.74 mm for Lithocarpus edulis (Nakai) when rainfall intensity was 5 and 50 mm h −1 .…”
Section: Bases For the Study Of Storage And Drainagementioning
confidence: 69%
See 4 more Smart Citations
“…These studies indicate that storage capacity of litter layers increased linearly to litter mass (Putuhena and Cordery, 1996;Sato et al, 2004). Also Sato et al (2004) demonstrated that rainfall intensity increased C min and C max of litter layers. For example C min increased from 0.44 to 1.03 mm for Cryptomeria japonica (D. Don) and from 1.33 to 1.74 mm for Lithocarpus edulis (Nakai) when rainfall intensity was 5 and 50 mm h −1 .…”
Section: Bases For the Study Of Storage And Drainagementioning
confidence: 69%
“…However, the mass of litter on the ground varies in space and time; species composition, wind, water, fire, animals and decay are important factors. Recent research in this field sampled the upper layer of the forest floor and analyzed interception under natural rainfall (Gerrits et al, 2007) or simulated rainfall (Pitman, 1989;TobonMarin et al, 2000;Sato et al, 2004). These studies indicate that storage capacity of litter layers increased linearly to litter mass (Putuhena and Cordery, 1996;Sato et al, 2004).…”
Section: Bases For the Study Of Storage And Drainagementioning
confidence: 99%
See 3 more Smart Citations